The Effect of Adding Cinnamon, Rosemary, and Thyme Oils on the Chemical Properties of Minced Local Lamb Meat During Frozen Storage - Al-Mafrigi, Imad Jasim Mohammed; Adnan Shukor Ahmed Al-Perkhdri (American Journal of Botany and Bioengineering, 2026)
This experiment was conducted in the laboratory of the Animal Production Department, College of Agriculture, University of Kirkuk, for a period of 60 days from 22/10/2025 to 21/12/2025. The aim was to study the effect of adding cinnamon, rosemary, and thyme oils on the chemical properties of minced local lamb meat during frozen storage. The thigh meat taken from local lambs was minced, the treatments were added, and the mixture was homogenized. The samples were distributed as follows: the control treatment without any addition, with meat stored for periods of 1, 30, and 60 days. Lambs fed on thyme powder 6g/kg of feed, lambs fed on rosemary powder 6g/kg of feed, lambs fed on cinnamon powder 6g/kg of feed, lambs fed on thyme powder 6g/kg of feed, and after slaughter, thyme oil was added at 0.06ml/kg of meat; lambs fed on rosemary powder 6g/kg of feed, and after slaughter, rosemary oil was added at 0.06ml/kg of meat; lambs fed on cinnamon powder 6g/kg of feed, and after slaughter, cinnamon oil was added at 0.06ml/kg of meat. With three replicates for each treatment, the transactions to which oils were added showed a decrease in moisture percentages. The first storage period recorded the highest percentage and a relative decrease in protein, while the second storage period was the best. There was an increase in ash and fat percentages for the treatments used in the study throughout the storage periods. From this, we can conclude that the treatments used had a clear effect on preserving the chemical composition of lamb meat, and that freezing storage played a role in maintaining the chemical qualities of the meat.